Role of Parental Smoking in Severe Bronchiolitis: A Hospital Based Case-Control Study - Rubina Farzana; Mujibul Hoque; Mohammad Shah Kamal; Md. Moseh Uddin Choudhury (International Journal of Pediatrics)
Objective. Bronchiolitis is one of the commonest causes of hospitalization of infants and young children in Bangladesh. About 21% of under 5 children attending different hospitals of Bangladesh have bronchiolitis. Fifty percent (50%) men and three percent (3%) women of Bangladesh are smokers. Parental smoking is an important risk factor for both susceptibility and severity of bronchiolitis. The aim of this study was to find out the role of parental smoking in severe bronchiolitis. Design. Case-control study. Place and Duration of Study. The study was conducted in the Department of Paediatrics, Sylhet MAG Osmani Medical College Hospital, Bangladesh, from July 2013 to December 2015. Patients and Methods. Sixty-four patients admitted into the ward with severe bronchiolitis were enrolled as cases and sixty-four suitably matched apparently healthy children attending EPI centre and outpatient department presenting with nonrespiratory illness were enrolled as controls. Sample size was calculated using Guilford and Frucher formula. The technique was systematic random sampling. Every second case satisfying the inclusion and exclusion criteria was enrolled in the study. Results. The mean age of the patients was 7.53 (SD ± 4.75) months. Forty (62.5%) patients were male and twenty four (37.5%) patients were female. Male-to-female ratio was 1.7 : 1. Most of the cases (60.95%) came from low socioeconomic background. More than half of the cases (53.13%) were not exclusively breastfed babies. Mean length of hospital stay was 6.41 (SD ± 2.82) days. Thirty eight (59%) cases and twenty six (34%) controls were exposed to parental smoking. Result was highly significant (p=0.005). Odds ratio was 2.8 (95% CI from 1.36 to 5.72). Conclusion. Exposure to parental smoking causes a statistically significant (p=0.005, odds ratio = 2.8) increase in the risk of developing severe bronchiolitis in the first year of life.